Research on on-machine measurement of machining error based on T-spline surface reconstruction. (19th August 2021) - Fu, Gaocai; Sheng, Buyun; Luo, Ruiping; Lu, Xincheng
Abstract: The machining quality of the parts can be directly inspected and analyzed through contact on-machine measurement. However, during the measurement of free-form surfaces, aiming at the problem that the spline surface fitting method requires too many measuring points and the original design information is not borrowed during reconstruction, a T-spline surface reconstruction method based on the centroidal Voronoi tessellation (CVT) sampling strategy is proposed. In the uv parameter region of the original designed NUBRS surface, the Gaussian curvature of the surface is taken as the regional density function, and the CVT is generated by the Lloyd algorithm. Based on the T-grid constructed by an adaptive quadtree method, three kinds of surface feature points are defined as measuring points. By using constrained optimization theory and hierarchical T-mesh knowledge, the generation and local optimization of T-spline surface based on the reconstruction of the original NUBRS surface control points is realized. At last, the example of the surface machined by Makino V77 machine tool and measured with BLUM TC60 probe shows that, the method in this paper can effectively fit a surface which is more suitable for actual processing by adjusting a relatively small number of control vertices with a limited number of measurement points.